Financial Performance Analysis at PT. Bank Syariah Mandiri With Method Economic Value Adde (Eva) - Hardana, Ali; Royani, Ida; Situmorang, Indah Sari; Ariyanda, Bima (Journal of Islamic Financial Technology, 2022)
PT. Bank Syariah Mandiri in the 2017-2019 period had a continuous increase in profit value, but from this value PT. Bank Syariah Mandiri has not been able to show the added economic value generated, because the profits obtained have not been deducted from the capital owned by PT. Mandiri Syariah Bank. This research is a quantitative research, using secondary data. The data used is time series data for 2017-2019 published by PT. Bank Syariah Mandiri through its official website, namely www.mandirisyariah.co.id . And analyzed using the Economic Value Added (EVA) method. Based on the results of research conducted by researchers, researchers concluded that PT. Bank Syariah Mandiri succeeded in creating economic added value, where overall in 2017-2019 the Economic Value Added (EVA) 0, and that means PT. Bank Syariah Mandiri obtained a positive Economic Value Added (EVA). And it's good that the results obtained with the EVA method are included in the bank's financial statements so that those who need financial reports can see the added value generated by the company.Keywords: Islamic Bank, Economic Value Added (EVA), Financial Performance